Auditing of enteral nutrition nursing care in critical care patients - Tahereh Al-Jalil; Golbahar Gray; Maryam Rasouli; Tooba Hoseini Azizi; Sima Sadat Hejazi* (Tehran University of Medical Sciences, 2019)
Background and Aim: Enteral nutrition standards noncompliance is one of the factors that threatens patient safety.  Auditing is an important part in quality improvement processes. The aim of this study was to determine enteral nutrition nursing care conformity rate with standards in the critical care units. Methods and Materials: In this descriptive study, 400 enteral feeding nursing care were assessed via time and event sampling methods. The tool was a researcher made check list in three fields: pre-feeding, feeding, and post feeding nursing care. Content validity and inter-rater coefficient reliability were calculated for checklist. The obtained data were analyzed using descriptive statistics. Results: The most conformity rate with standards was in feeding (86%), pre-feeding (3/8 %) and post feeding (2/3%) field, respectively. Determination of PH (100%) and accurate gastric residual volume (99.8%) in pre-feeding field, disconnection of the syringe from catheter after feeding, in feeding filed and accurate documentation of the care (99.3%) in post feeding field, were not implemented in the most of cases. Conclusion: Enteral nutrition nursing care is far from standards in the pre and post feeding fields. Lack of the clear clinical guidelines, shortage of nursing staff and equipment and inadequate training are relating factors.